Bilateral pyogenic psoas abscesses with inferior vena cava thrombosis. - Ab. Hamid, Suzana; Abdullah, Basri Johan Jeet (Hong Kong Academy of Medicine Press., 2008)
Psoas abscess is a rare clinical entity. Rarely, it is associated with thrombosis of the inferior vena cava. This report is of a 36-year-old woman with bilateral pyogenic psoas abscesses with spondylodiscitis complicated by thrombosis of the inferior vena cava. The pathogenesis and imaging features of this condition are discussed.